Nature Diction of Farmer’s Children in Indonesian Agrarian Poetry Anthology (Ecocritical Review) - Rahmania Rasyid; Azis Azis; Suarni Syam Saguni (HUMAN: South Asian Journal of Social Studies, 2021)
Abstract. This study aims to describe the value of ecological wisdom based on Glotfelty's ecocritical study. This research is a descriptive qualitative research. The data of this research are statements or text excerpts in a collection of Indonesian agrarian poems that describe nature's diction in the value of ecological wisdom. This research is an anthology of Indonesian agrarian poetry. The analysis of this research was carried out by identifying, classifying, analyzing, and describing the natural diction of ecological wisdom in a collection of Indonesian agrarian poetry, Glotfelty's ecocritic study. The results of this study indicate that there are several values of ecological wisdom. The value of ecological wisdom is divided into five namely, respect for nature, the principle of responsibility to nature, the principle of compassion and care for nature, the principle of not harming nature, and the principle of living is simple and in harmony with nature.